Peter van Inwagen Materialism, Free Will and God (Münster Lectures in Philosophy,, 2018)
This book discusses the philosophy of influential contemporary philosopher Peter van Inwagen. Looking at perennial philosophical problems from a modern point of view, Peter van Inwagen's philosophy masterfully combines positions that have been considered irreconcilable: incompatibilism concerning free will, materialism, organicism, theism and realism concerning fictional entities. As readers will discover, his arguments are witty, surprising and deep. The book includes Peter van Inwagen's Münster Lecture of 2015 on free will, as well as eleven papers from the Münster colloquium discussing central themes of his philosophy, and a reply to each paper by Peter van Inwagen himself. Introducing his philosophy and relating his work to other contemporary views, this book is of interest to graduate students and professionals in philosophy alike.